Implementasi AHP (Analytical Hierarchy Process) pada Sistem Proteksi Optical Line Termination Berbasis IoT - Ahmad Iqbal Fariky; Elvianto Dwi Hartono (Journal of Informatic and Information Security, 2022)
The development of increasingly advanced technology follows the needs of the community, one of which is in the telecommunications world, namely FTTH (Fiber to the Home), a form of optical signal transmission from the service provider to the customer's home and optical fiber as a delivery medium. Deploying with FTTH technology can save costs and reduce operating costs and provide better services to customers. The OLT is connected to Fiber to the Home (FTTH). OLT or short for Optical Line Terminal, is an endpoint equipment in a passive optical network (PON). One of the problems faced is the unavailability of a monitoring system to determine the condition of the Optical Line Terminal device remotely. This tool monitoring system can monitor outdoor units based on unit humidity, control unit temperature based on air temperature conditions, detect fire with infrared sensors and ensure unit security with RFID. In this device, the device temperature monitor uses a maximum temperature input of 40 degrees Celsius and aheating fan power to increase the temperature. The DHT11 sensor detects device humidity based on humidity levels. For temperature control, the input temperature is not more or less than 20 - 40 °C. The output is in the form of turning on and off the heater or fan. For control conditions the humidity limit is not more than 30%. The remote monitoring system can display data on temperature, humidity, fire detection and security locks with RFID.